Hungarian Monitoring, 1 November 1989 . [Magyar rádiófigyelő], 1989. november 1 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Situation in the GDR: economic problems, Krenz in Moscow Domestic Affairs: - European Parliament Christian Democratic faction in Hungary - Hungarian Socialist Party (MSZP) presidium meeting - Premier meets oppositionists - Hungarian parties failed to distribute HUF 100 million released by government - Smallholders' Party committee meeting - Ferenc Morvai does not trust the Hungarian Academy of Sciences's research into Petőfi's remains Economy: - Cooperation with EFTA - Jenő Rednágel on free prices - National Association of Entrepreneurs (VOSZ) discussions Külpolitika: - NDK helyzet: gazdasági gondok, Krenz Moszkvában Belpolitika: - Hazánkban az EP kereszténydemokrata frakciója - MSZP pártelnökség ülés - Ellenzékiekkel tárgyalt a kormányfő - A magyar pártok estig nem tudták elosztani a kormány által rendelkezésre bocsátott 100 millió forintot - A Kisgazdapárt választmányi ülése - Morvai Ferenc nem bízik az Akadémia Petőfi kutatásaiban Gazdaság: - Együttműködés az EFTA-val - Rednágel Jenő a szabad árakról - VOSZ tanácskozás